Indústria 4.0 e recursos humanos: superestimando a tecnologia e subestimando os recursos humanos - Paula Sylvia Ridolfi Aguiar Carrara (2023)
This research presents topics regarding human resources that have emerged in the context of national and international scientific production on Industry 4.0. The search, selection, collection and classification of scientific articles were based on the Methodi Ordinatio and the analysis was performed using the bibliometric method of co-occurrences. The search itself was developed on the Web of Science Core Collection and the bibliometric analysis used the VOSviewer software. The 3,413 selected articles on Industry 4.0 were classified into 5 clusters: 1) macro overview; 2) technical and organizational factors; 3) structure; 4) big data and analytics; 5) technological integration challenges. Regarding human resources, 101 articles with the most frequent topics were reviewed, generating a co-occurrence map containing 38 keywords, 401 links and 4 clusters: 1) future of work and the dynamics of change in HR; 2) organizational support, development of skills and overcoming barriers; 3) the relation between HR, technological advances, intellectual capital, innovation, creativity and organizational performance; 4) underlying managerial challenges. The study is original for providing an overview of human resources when adopting Industry 4.0, covering the main areas in a single research, which might serve as a guide for future investigations. From a pragmatic approach, it might be useful when addressing the opportunities and challenges of human resource management and supporting the digital transition of organizations. The research found that virtually all human resource management processes, as well as human behavior in organizations and work relations, have been studied, but in a inferior number compared to studies related to technical and technological aspects. Evidence is that interest in the human factor in the context of Industry 4.0 has grown over the years.